Proceedings of the International Symposium for Next Generation Infrastructure 2014
DOI: 10.14453/isngi2013.proc.44
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Extreme Risks in Critical Infrastructure Interdependencies

Abstract: Critical infrastructures like our power generation facilities and water supply form highly interconnected networks that are mutually dependent and any failure can cascade through the network, resulting in devastating impact on health, safety and the economy. These catastrophic events/disruptions can be triggered by environmental accidents, geological/weather phenomena, disease pandemics, etc. The disruptions can be caused/exacerbated by their being unexpected, but they may actually be expected if relevant data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Considering that the complexity and heterogeneity of networks built in a company's specific environment have simultaneously reduced the efficiency of network administrators [39], vulnerabilities assessment and analysis regularly can support the employees in giving the confidence in order to prepare themselves through training and understanding for proper control and handling 1651 activity. It is doubtful that some modeling and analysis could accurately and clearly predict how such an attack would occur on the network infrastructure, resulting in a shutdown or disruption, followed by a collision as the consequences [40], [41]. But at the very least, it can presents a depiction and alternative solution for prediction and preparation for the organization.…”
Section: Walkthrough Analysis With Vulnixmentioning
confidence: 99%
“…Considering that the complexity and heterogeneity of networks built in a company's specific environment have simultaneously reduced the efficiency of network administrators [39], vulnerabilities assessment and analysis regularly can support the employees in giving the confidence in order to prepare themselves through training and understanding for proper control and handling 1651 activity. It is doubtful that some modeling and analysis could accurately and clearly predict how such an attack would occur on the network infrastructure, resulting in a shutdown or disruption, followed by a collision as the consequences [40], [41]. But at the very least, it can presents a depiction and alternative solution for prediction and preparation for the organization.…”
Section: Walkthrough Analysis With Vulnixmentioning
confidence: 99%
“…Since critical infrastructure can be described through its network and the linkage between infrastructures can be used to describe the inter-relations among them, the network approach becomes a natural candidate for interdependency studies. The performance of an infrastructure can be analysed by modelling the component failure from the hazard at a component level, and then simulating the cascading failure within the modelled network at a system level (Tai et al, 2013). Lam et al (2013) demonstrated that by modelling the relationships and observing how disruption cascades within a complex infrastructure system, vulnerabilities can be identified, enabling planning for recovery and response.…”
Section: Network Approachmentioning
confidence: 99%
“…Understanding the large-scale critical infrastructure network and its interdependencies can help us identify the interdependent links and their corresponding strengths (Santos et al, 2007;Wang et al, 2013;Tai et al, 2013;Kizhakkedath et al, 2013), and enables the development of a model to evaluate and predict the impact of a disruption, including the cascading and overall impact to economic sectors that are linked by these interdependencies. This can aid stakeholders in analysing worst case scenarios (Lam et al, 2013;Lin et al, 2016a;Lin et al, 2016b) These advantages may be helpful in the current research as critical infrastructure network analysis requires a model that is able to link infrastructure together, according to physical and logical interdependencies (Rinaldi et al, 2001).…”
Section: The Nature Of the I/o Model And Its Suitability For Critical Infrastructure Interdependency Modellingmentioning
confidence: 99%
See 1 more Smart Citation